What are the causes for the failure of euccessful cadet and junior Iranian wrestlers to continue their success as seniors? The coaches' perspective - Khodayari, A.; Babaei Jafari, M.; Asgari, B.; Babaei Jafari, A. (International Journal of Wrestling Science, 2014)
The purpose of this research is to identify the causes for the failure of successful cadet and junior Iranian cadet and junior wrestlers to continue their success as seniors, from the perspective of the coaches. The research sample was selected randomly and is included 162 people from grade 1 and 2 of active coaches of Iran. This research used a researcher-made questionnaire containing 35 questions in five subscales including program resources, management, physical fitness, sport injuries and psychological problems. The validity of this questionnaire was established by a review of 7 experts of physical education, and also in a pilot study using 30 experts. The questionnaire reliability was established using Cronbach's alpha yielded an r value of 0.80. The data analysis utilized descriptive and inferential statistical (Friedman test) in SPSS software and a significance level of p<0.05. Results showed that the factor with the greatest impact on the failure of cadet and junior medalists in senior wrestling was program resources, followed by, management, sport injuries, physical fitness and psychological problems, respectively. It is recommended that wrestling federation officials prioritize these subscales to maintain the development of cadet and junior medalists so they continue on as successful senior wrestlers.